Image processing of robotic eyes - Deng, Xin (2013)
In many situations, cameras are used to capture live videos. However most of these cameras can only capture images from a fixed range since the camera are fixed at a point. This project aims to built a pair of robotic eyes that will track the moving object. For image processing, simulink is used to process images acquired by webcams to determine the moving object. By sending the coordinates of the target object to the hardware controller, the webcams would be able track the moving object and activate the actuators. [4th Award]